Radiostereometric analysis using clinical radiographic views: Validation with model-based radiostereometric analysis for the knee. (August 2018) - Yuan, Xunhua; Broberg, Jordan S; Naudie, Douglas DR; Holdsworth, David W; Teeter, Matthew G
Radiostereometric analysis is a sophisticated radiographic technique with high measurement accuracy. In order to improve the accessibility of radiostereometric analysis for clinical use, a modified radiostereometric analysis procedure has been previously proposed that enables clinical radiographic views to be used for radiostereometric analysis. It has been successfully validated for its application to the hip wear study with the conventional bead–based radiostereometric analysis environment using computed radiography. In this study, we describe the implementation and validation of this technique for the knee study with the model-based radiostereometric analysis environment using digital radiography. A knee-joint phantom with 6 degrees of freedom was examined, and the bias and repeatability/reproducibility of the modified radiostereometric analysis approach were investigated following the newly updated ASTM recommendations. The bias parameters (mean ± 95% confidence interval) ranged from 0.008 ± 0.003 mm to 0.027 ± 0.006 mm for translation and from 0.014° ± 0.007° to 0.040° ± 0.020° for rotation. The repeatability standard deviation ranged from 0.004 to 0.020 mm for translation and from 0.005° to 0.015° for rotation. The 95% repeatability limit ranged from 0.011 to 0.055 mm for translation and from 0.014° to 0.041° for rotation. The reproducibility standard deviation ranged from 0.004 to 0.023 mm for translation and from 0.006° to 0.040° for rotation. The 95% reproducibility limit ranged from 0.012 to 0.063 mm for translation and from 0.016° to 0.112° for rotation. The modified procedure allows routine clinical radiographs to be used for radiostereometric analysis, which provides the possibility of adding quantitative measurements to current patient registries.